2016
DOI: 10.5372/1905-7415.1002.471
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting mortality of elderly patients with acute upper gastrointestinal bleeding

Abstract: Background: Acute upper gastrointestinal bleeding (UGIB) is a common gastrointestinal disease emergency and a cause of morbidity and mortality. Objectives: To assess the clinical outcomes and explore predictive factors for mortality of elderly patients with acute UGIB. Methods: During the study period from January 2010 to September 2011, we prospectively enrolled 981 patients presenting with UGIB from 11 hospitals (mean age ± standard deviation (SD), 59.4 ± 14.9 years; range, 17−94 years; including 661 men). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…On the contrary to our results, bleeding peptic ulcer was reported as the main source of UGIB among elderly in several studies: Thongbai et al [ 3 ] stated that the most common cause of acute UGIB was peptic ulcer bleeding which accounted for 84.8% of UGIB in their elderly patients. Also Charatcharoenwitthaya et al [ 12 ] found that 68% of acute UGIB was derived from bleeding peptic ulcers which were attributed to increase prescribing of potentially ulcerogenic drugs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On the contrary to our results, bleeding peptic ulcer was reported as the main source of UGIB among elderly in several studies: Thongbai et al [ 3 ] stated that the most common cause of acute UGIB was peptic ulcer bleeding which accounted for 84.8% of UGIB in their elderly patients. Also Charatcharoenwitthaya et al [ 12 ] found that 68% of acute UGIB was derived from bleeding peptic ulcers which were attributed to increase prescribing of potentially ulcerogenic drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar result was obtained by Nahon et al [ 17 ] who revealed that in-hospital mortality rate of the elderly was 8.93%. On the other hand, low mortality rate of 3.41% was reported in a study of Thongbai et al [ 3 ] who attributed that to small number of cirrhotic portal hypertensive patients (11.22%)—who carried a higher risk of mortality—included in their study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thongbai et al [1] have conducted a multicenter study from 11 hospitals in Thailand and identify predictors of 30 day mortality among the elderly. These include a pulse rate of more than 100 beats per minute at first visit, red cells in nasogastric aspiration, existing coronary heart disease, and creatinine of >1.5 mg/dL.…”
mentioning
confidence: 99%
“…All the existing scores including the predictors suggested by Thongbai et al [1] need to be validated in appropriate populations to guide treatment, reduce the length of hospital stay and the cost associated with treatment, and the rate of admission.…”
mentioning
confidence: 99%